Konflik Berkepanjangan Antara Israel Dan Palestina Dan Tantangan Implementasi Hukum Humaniter Dalam Resolusi Internasional - Napitupulu, Faisal Florance; Triandoko, Febi; Susilo, Tarsisius; Apandi, Asep; Dhani Broto Nugroho, Sidik (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The prolonged conflict between Israel and Palestine, particularly in the Gaza Strip, has resulted in severe humanitarian consequences and drawn widespread international concern. This study aims to analyze violations of International Humanitarian Law (IHL) committed by parties involved in the conflict, focusing on the protection of civilians, access to humanitarian aid, and legal accountability for those responsible. Using a qualitative approach and literature review from reports issued by the United Nations, non-governmental organizations such as Human Rights Watch, the International Committee of the Red Cross (ICRC), and international legal bodies such as the International Criminal Court (ICC), the study finds strong indications of collective punishment, disproportionate attacks, and restrictions on essential aid—all of which contradict fundamental principles of IHL. Furthermore, this research highlights the failure of international mechanisms to enforce justice effectively for victims, particularly children and other vulnerable groups in Gaza. Upholding accountability, non-discrimination, and legal protections for civilians are critical components in preventing future violations and building a sustainable foundation for peace in the region.